Colonic biliar ileus. Regarding two cases.: A propósito de dos casos. - Armand Ugon, César; Schneeberger, Federico; Gutiérrez, Fernando (Cirugía del Uruguay, 1988)
Two cases of colonic biliar ileus lead the authors to a revision of the subject. They emphasize the fact that bi• liar ileus have features that differenciate them from each other, which is why the preoperative diagnosis is exceptional, particularly because of the rareness of the colonic localization.